Optimizing employee productivity: The mediating role of employee engagement in training programs for Malaysian SMEs - Arokiasamy, Anantha Raj A; Wider, Walton; Tanucan, Jem Cloyd M; Hossain, Syed Far Abid (Asian Development Policy Review, 2025)
Small and medium-sized enterprises (SMEs) are essential to Malaysia’s economy, forming a substantial portion of corporate entities and fueling employment and economic growth. However, challenges such as limited resources and high turnover necessitate strategies to enhance employee productivity (EP). This study investigates the influence of training programs on EP in Malaysian SMEs, emphasizing employee engagement as a mediator. Grounded in Human Capital Theory (HCT), Social Exchange Theory (SET), and the Job Demands-Resources (JD-R) Model, it explores how training boosts skills and engagement, subsequently improving productivity. A quantitative approach was employed, collecting data via structured surveys from 300 SME employees across diverse sectors who participated in formal training within the past year. Structural Equation Modeling (SEM) confirmed that training significantly enhances EP (β=0.274, p<0.001, H1) and engagement (β=0.288, p<0.001, H2), with engagement mediating the training-productivity relationship (β=0.239, p<0.001, H3). These findings underscore training’s dual role in skill development and fostering engagement, amplifying productivity in resource-constrained settings. Practically, SME managers should leverage cost-effective e-learning and align training with organizational goals, while policymakers could support subsidies to bolster SME competitiveness. Limitations include the cross-sectional design, self-reported data biases, and focus on Malaysian SMEs, limiting generalizability. Future research may adopt longitudinal methods, cross-cultural comparisons, and probabilistic sampling to deepen insights into training’s long-term effects and broader applicability. This study enriches organizational development literature by contextualizing training and engagement dynamics in emerging economies.